Designated Person Ashore – how they perceive their role in the organization and to which extent they believe they are legally exposed in case of an accident - Sollien, Ketil (My University, 2012)
The main objective of this project was to study how the DPA's perceive their role in the organization in relation to the ISM Code's requirements and to which extent they believe they can be legally exposed in case of an accident. To what extent could a DPA be charged with negligence was one of the questions. A part of this was to study the organizational models and analyze these against the requirements and expectations of the ISM Code. The background for this study is the many articles written about the DPA's role in the organization and the interpretation of the responsibility in relation to the ISM Code after an accident. Part of this study was to test this hypothesis. The method used is interviews with four DPA's working for shipping Companies and two other experts in this field. In addition to this e-mail exchange with other professional bodies, discussions with active DPA's and study of relevant literature. It looks like the theory that triggered this thesis is not quite correct. It looks like all gloomy predictions following the introduction of the ISM Code have turned and this debate has subsided. During this study I have noticed the absence of recent debate in this field and little attention from the accident reports also indicates this. Despite this there is still some uncertainty about this among maritime actors. ISM Code expects continuous improvement in safety on board. The DPA is responsible for determining the effectiveness of the safety management system within the company and onboard the ship. The weakness of the ISM Code as I see it that it does not clearly define what is "top management" and therefore does not make clear demands on how high up in the system to DPA should report. The question is therefore whether this had been an improvement (continuous improvement process is part of the target with the Code), and whether it is practically feasible. This thesis shows that to succeed in this role he/she is dependent of a good cooperation with other departments and full support from top management.
Keywords: Datorsystem; Farkostteknik; Computer Systems; Vehicle Engineering